2018
DOI: 10.1111/1467-8500.12325
|View full text |Cite
|
Sign up to set email alerts
|

Personal values and value congruence of public administration graduate students: An exploratory study in China

Abstract: Explorations on the value profiles of current and prospective public organisation employees in China are scarce. The current study investigates this critical issue. Data were collected via a questionnaire from graduate students enrolled in a school of public administration in China. The sample consisted of both full‐time students who were prepared to pursue their careers in public organisations upon graduation, and part‐time students who were mostly public organisation employees. Multivariate analyses of covar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 90 publications
1
2
0
Order By: Relevance
“…Regarding the dichotomy public vs. private sector, it is interesting to observe that MSc students-older and more experienced-tend to be more optimistic about the public sector as opposed to undergrad students who show a predisposition for the private sector. This different pattern of choice, depending on cycle of studies and age, has been found elsewhere (e.g., [43,45]). Moreover, the public sector is generally perceived as lacking the capacity for innovation and a stimulating work environment, as opposed to the private sector, with the exception of students from Exact and Medical Sciences.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Regarding the dichotomy public vs. private sector, it is interesting to observe that MSc students-older and more experienced-tend to be more optimistic about the public sector as opposed to undergrad students who show a predisposition for the private sector. This different pattern of choice, depending on cycle of studies and age, has been found elsewhere (e.g., [43,45]). Moreover, the public sector is generally perceived as lacking the capacity for innovation and a stimulating work environment, as opposed to the private sector, with the exception of students from Exact and Medical Sciences.…”
Section: Discussionsupporting
confidence: 54%
“…The literature is not consensual regarding this pattern and cultural-based differences may impair a valid comparison, given different values system. For instance, a more collectivist system, in the case of Zhong and Bao [45], shows that older Chinese students are more concerned with altruistic values than younger ones. Pondering on these results requires keeping in mind a comprehensive socialisation model and a sharp questioning of what is being fostered during these formation years.…”
Section: Discussionmentioning
confidence: 99%
“…However, such studies are mostly conducted in Western contexts. Few efforts have been made, in either Chinese or English, to compare the work values of employees across sectors in China (Zhong and Bao 2018). Sectoral differences in employee work values in the country are best characterized as ambiguous, particularly in public organizations.…”
Section: Introductionmentioning
confidence: 99%